ANALISIS SEBARAN SPASIAL TINGKAT KESUBURAN TANAH DI KECAMATAN LEMBO KABUPATEN KONAWE UTARA - Lasahari, Fitra Asgianti; Hidayat, Ahmad; Hadini, La Ode (Sustainability (STPP) Theory, Practice and Policy, 2024)
Lembo Sub-district possesses extensive agricultural land with the potential to achieve sustainable food self-sufficiency through appropriate land use. This research aims to analyze soil fertility levels and determine the spatial distribution of soil fertility in Lembo Sub-district, North Konawe Regency. The parameters of this study include: C-organic, base saturation (KB), phosphorus pentoxide (P2O5), potassium oxide (K2O5), and cation exchange capacity (CEC). Materials used in this study include: SHP of Lembo Sub-district, soil type maps, and DEMNAS data. Data were obtained from observations at seven locations and laboratory analysis. The analysis methods used are spatial analysis and quantitative descriptive analysis. The results indicate that: the highest CEC value is 24.60 me/100g and the lowest is 19.80 me/100g; the highest base saturation is 48.70% and the lowest is 29.80%; the highest P2O5 value is 16.90 ppm and the lowest is 12.70 ppm. The highest K2O5 value is 25.10 me/100g and the lowest is 17.90 me/100g. The highest C-organic value is 1.90% and the lowest is 0.70%. Spatially, soil fertility across Lembo Sub-district is categorized as low (R).